STRENGTHENING HISTORY LEARNING AT SMAN 2 MEDAN: BUILDING CHARACTER AND NATIONAL INSIGHT - Ubaidillah, Ubaidillah; Sumantri, Pulung; Aisyah, Sitti (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study aims to analyze the strengthening of history learning at SMA Negeri 2 Medan in building students' character and national insight. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, documentation studies, and questionnaires. The results of the study show that the application of interactive learning methods such as problem-based learning and project-based learning, as well as the use of digital technology in history learning, is able to increase students' understanding of history materials. In addition, history teaching at this school is effective in instilling character values such as honesty, responsibility, discipline, and love for the homeland. Curriculum that integrates local history and extracurricular activities, such as museum visits and nationality seminars, also contributes to broadening students' national horizons. However, the study also found several challenges, including a lack of student interest in history lessons and limited access to technology. Support from teachers, parents, and the community is very important in overcoming these obstacles. Overall, the strengthening of history learning at SMA Negeri 2 Medan has a positive impact on shaping students' character and increasing their national insight.